Connectivity of the human pedunculopontine nucleus region and diffusion tensor imaging in surgical targeting. - Muthusamy, K; Aravamuthan, B; Kringelbach, M; Jenkinson, N; Voets, N; Johansen-Berg, H; Stein, J; Aziz, T (2007)
OBJECT: The pedunculopontine nucleus (PPN) region of the brainstem has become a new stimulation target for the treatment of gait freezing, akinesia, and postural instability in advanced Parkinson disease (PD). Because PD locomotor symptoms are probably caused by excessive gamma-aminobutyric acidergic inhibition of the PPN, low-frequency stimulation of the PPN may overcome this inhibition and improve the symptoms. However, the anatomical connections of this region in humans are not known in any detail. METHODS: Diffusion weighted magnetic resonance (MR) images were acquired at 1.5 teslas, and probabilistic tractography was used to trace the connections of the PPN region in eight healthy volunteers. A single seed voxel (2 x 2 x 2 mm) was chosen in the PPN just lateral to the decussation of the superior cerebellar peduncle, and the Diffusion Toolbox of the Oxford Centre for Functional Magnetic Resonance Imaging of the Brain was used to process the acquired MR images. The connections of each volunteer's PPN region were analyzed using a human brain MR imaging atlas. RESULTS: The PPN region was connected with the cerebellum and spinal cord below and to the thalamus, pallidum, subthalamic nucleus, and motor cortex above. The regions of the primary motor cortex that control the trunk and upper and lower extremities had the highest connectivity compared with other parts of motor cortex. CONCLUSIONS: These findings suggest that connections of the PPN region with the primary motor cortex, basal ganglia, thalamus, cerebellum, and spinal cord may play important roles in the regulation of movement by the PPN region. Diffusion tensor imaging tractography of the PPN region may be used preoperatively to optimize placement of stimulation electrodes and postoperatively it may also be useful to reassess electrode positions.